Wordlikeness and word learning in children with hearing loss. Issue 2 (29th October 2012) - Stiles, Derek J.; McGregor, Karla K.; Bentler, Ruth A.
Abstract: Background: The more a novel word conforms to the phonotactics of the language, the more wordlike it is and the easier it is to learn. It is unknown to what extent children with hearing loss (CHL) take advantage of phonotactic cues to support word learning. Aims: This study investigated whether CHL had similar sensitivities to wordlikeness during a word‐learning task as children with normal hearing (CNH). Methods & Procedures: Sixteen CHL and 24 CNH participated in a novel word‐learning task. Novel words varied by English wordlikeness. Recall was tested using a forced‐choice identification task wherein foils for each trial related semantically, lexically or not at all. Receptive vocabulary and working memory were also assessed. Outcomes & Results: All children were able to identify high wordlike novel words more accurately than low wordlike novel words. The number of errors on identification of words that were moderate in wordlikeness was inversely correlated to vocabulary size (not working memory) and CHL had smaller vocabularies than CNH. When in error, CHL were more likely than CNH to select a semantically related foil. Conclusions & Implications: Although they are sensitive to extremes in wordlikeness, compared with their peers with normal hearing, CHL present with subtle differences in word learning. Clinical implications for exploiting wordlikeness in service of word learning assessment and intervention are presented.